The Relationship Between Nurses' Quality of Work-Life on Organizational Loyalty and Job Performance in Saudi Arabian Hospitals: A Cross-Sectional Study - Al-Dossary, Reem N (Frontiers in Public Health, 2022)
Purpose: The purpose of this study is to analyze the impact of quality of work-life on the organizational loyalty and job performance in Saudi Arabia Methods: This study used a cross-sectional design for collecting the data related to nurses’ quality of work-life, organizational loyalty, and job performance from nursing staff in Saudi Arabian hospitals. Three questionnaires were used in this study, which include Quality of Work Life Scale (QWLS), Organizational Commitment Questionnaire (OCQ), and Individual Work Performance Questionnaire (IWPQ). An online version of the survey questionnaire was generated using Google survey, to which a link is generated for collecting data. At the end of the survey, 243 responses were received. After removing the incomplete responses, 209 responses were considered for the data analysis. Statistical techniques including t-tests, and Pearson’s correlation were used in data analysis. Results: Nurse managers reflected good quality of life, and high loyalty towards their employers, and also reflected good job performance levels. However, staff nurses reflected poor quality of work-life, organizational loyalty, and job performance. Training and development had strong positive correlation with continuance commitment (r=.628, p<.01). Job satisfaction and job security held strong positive correlation with task performance (r=.601, p<.01) and contextual performance (r=.601, p<.01). Conclusion: Quality of work-life, organization loyalty, and job performance are positively correlated, and poor quality of work-life can negatively impact job performance and organizational loyalty of nurses.